SUPPLY CHAIN DISRUPTION AND PERFORMANCE OF PLASTIC MANUFACTURING FIRMS IN ANAMBRA STATE, NIGERIA. - Hope N. Nzewi, PhD; Obianuju M. Chiekezie, PhD and Bankole I. Akinroluyo (Journal of the Management Sciences, 2024)
The business environment is characterized by uncertainties, external factors, complexities, internal forces and linkages where supply chains generate influence in the viability and sustenance of firms across industries. However, supply chain disruptions have great tendencies to constrain the efficient performance and strategies of companies in the manufacturing sector. Therefore, this study examines supply chain disruption determinants and performance of plastic manufacturing firms in Anambra state. Specifically, it; (i) ascertained the extent of relationship between supply chain disruption and performance of plastic manufacturing firms in Anambra state; and (ii) determined the effect of inventory shortages on profit- after tax of plastic manufacturing firms in Anambra State. Survey research design was employed and structured questionnaire was used to collect the data. The data were analyzed using correlation and regression through SPSS v23. The result indicated that there is a strong negative relationship between supply chain disruption and performance of plastic manufacturing firms with R= -.758. Inventory shortage has negative effect on profit- after tax of plastic manufacturing firms with B= -.932 and R square= 76.1%. The study concluded that supply chain disruption determinant has significant effect on the performance of plastic manufacturing firms. We therefore, recommend that plastic firms need to diversify suppliers, invest in technology for improved visibility and tracking to mitigate the impact of disruptions on the performance and profit after tax of plastic manufacturing firms.